(3OjhGf YHOGdQVG GdcGXejs - (3YHO GdQVG Hf CMeO Hf NdjaI GdebQj GdTQja GdcGXej,J (B1120 (3g` s ((3eMeO GdSeGhj s)
(3ChdgG (B:s
(3CTgO Gddg Cffj CTgO Cf dG Edg EdG Gddg GdCRdj cGf ef bHd cd TF hjHbi Mjf dG Mj ZjQg hgh Mj s
(3BNQgG (B:s
(3Udi GdEdg Ydjce eG ESJfGQ VMi heG jHOQ GdOLi oMaJ OQGQjg s
(3GdOjhGf aj eOM GdCFeI ef Cgd GdHjJ Ydjge GdSdGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B220s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B152 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHIBjI Gddg GdMcje GdYGeI HGdfLa (B(278) s
Keywords: (3GdCOHs